Bortezomib for refractory acute antibody‐mediated rejection in kidney transplant recipients: A single‐centre case series. Issue 8 (August 2016) - De Sousa‐Amorim, Erika; Revuelta, Ignacio; Diekmann, Fritz; Cofan, Frederic; Lozano, Miquel; Cid, Joan; Palou, Eduard; Sole, Manel; Campistol, Josep María; Oppenheimer, Federic
Abstract: Aim: Acute antibody‐mediated rejection (ABMR) after kidney transplantation (KT) is associated with poor allograft survival. Current therapies for ABMR are able to deplete B‐lymphocytes but do not target plasma cells. Bortezomib is a proteasome inhibitor that can eliminate plasma cells and has demonstrated utility in the treatment of ABMR. Methods: A retrospective study was carried out from 2010 to 2014, including all patients with ABMR refractory to conventional treatment who received bortezomib. Bortezomib (1.3 mg/m 2 ) was administered intravenously on days 1, 4, 8, and 11. Renal function, graft survival, follow‐up biopsies, and donor‐specific antibodies (DSA) were recorded. Results: We identified seven patients. Of these, high immunological risk was found in 6 of 7, preformed DSA were found in 5 of 7, flow cytometry crossmatch was positive in 4 of 7, and desensitization before KTx was provided in 6 of 7 patients. ABMR was diagnosed at a median of 90 days (8‐167) post‐KT. After bortezomib therapy, renal function improved or stabilized in 5 of 7 patients and progressively deteriorated in 2 of 7, leading to haemodialysis after 7 and 11 months, respectively. Follow‐up kidney biopsies showed persistence of ABMR in 2 of 7, chronic active ABMR 3 of 7 and inactive chronic lesions in 2 of 7. DSA titres significantly decreased after treatment ( P  = 0.028). All patients experienced mild adverse events. After a follow‐up of 22 ± 18 months, three grafts were lost (42%) and four remained functioning. Conclusion: Bortezomib could be useful as an adjuvant therapy for ABMR refractory to conventional treatment with acceptable mid‐term outcomes in these severe cases. More research is needed to develop strategies to better preserve graft function after refractory ABMR. SUMMARY AT A GLANCE: This manuscript describes the use of bortezomib in seven renal transplant cases with refractory acute antibody‐mediated rejection. As with most of these small retrospective uncontrolled case studies, the actual benefit of bortezomib remains unclear. Nevertheless the patient outcomes (reasonable in the medium term), and side effects experienced are useful to review. Further studies examining this therapy are still required however.